THE DEVELOPMENT OF “KOMLABIL” (KOMIK POLA BILANGAN) MEDIA IN LEARNING NUMERICAL PATTERNS - Machmud, Tedy; Hulopi, Renata; Damayanti, Taulia (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
In the era of globalization, marked by the rapid development of technology, various innovations continue to emerge, including in the education sector. The application of digital transformation in education involves the use of information and communication technology to impact the improvement of learning quality, expand access to learning resources, and create a more interactive and collaborative learning environment. Thus, the education sector has become one of the most responsive fields to technological advancements. This study developed a learning media in the form of comics, named "Komlabil," using i-Spring Suite software on the material of numerical patterns. This media was designed following the PLOMP development model which includes five main stages: Preliminary Investigation, Design, Realization/Construction, Test, Evaluation and Revision, and Implementation. The research subjects were 27 eighth-grade students at SMP Negeri 1 Bulawa. This study revealed that digital comic media has been declared valid and practical. Through evaluation by media and material expert validators, an average score of 3.27 was obtained from the media expert evaluation and 3.34 from the material expert, both of which fall into the valid category. This indicates that the developed digital comics meet the expected quality standards, both in design and material content, making it suitable to be used as a supporting tool in learning. The percentage of student and teacher responses obtained 92.37% with a strongly positive category and 89% with a practical category. Based on these findings, the developed learning media is considered suitable to be used in teaching and learning activities because it meets the predetermined criteria of validity and practicality. Thus, this learning media not only meets rigorous academic standards but also contributes significantly to improving the quality of the learning process.